2017
DOI: 10.1093/annonc/mdx398
|View full text |Cite
|
Sign up to set email alerts
|

Open access to journal articles in oncology: current situation and citation impact

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
0
15
0
2
Order By: Relevance
“…However, findings of another study by Nazim & Zia 2 revealed that 58.44 per cent OA articles were accessible through green route. Similarly, a study by Hua, et al 38 found that 58 per cent articles were available through gold OA in the field of oncology, where 34 per cent articles were accessible via OA journals (gold OA), and 46 per cent articles through self-archiving (green OA).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, findings of another study by Nazim & Zia 2 revealed that 58.44 per cent OA articles were accessible through green route. Similarly, a study by Hua, et al 38 found that 58 per cent articles were available through gold OA in the field of oncology, where 34 per cent articles were accessible via OA journals (gold OA), and 46 per cent articles through self-archiving (green OA).…”
Section: Discussionmentioning
confidence: 94%
“…However, nazim & Zia in recent studies; reported that researchers in Indian Institutes of Technology and AMU were mostly use ResearchGate and IRs for self-archiving of their research work. Another study by Hua, et al 38 also found that ResearchGate and the PMC were the main venues for providing articles openly accessible in the field of oncology.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that open-access articles are cited at a higher rate compared to those requiring subscription. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…The reason being that those who download and/or read it are not by definition publishing scientists themselves. Subsequently, studies demonstrate that OA has limited or no effect on impact factors [ 4 , 6 , 7 ].…”
Section: Article Processing Charge Predatory Journals and Big Dealsmentioning
confidence: 99%